2006
DOI: 10.1002/bip.20610
|View full text |Cite|
|
Sign up to set email alerts
|

Effects of gamma radiation on β‐lactoglobulin: Oligomerization and aggregation

Abstract: The conformational changes and aggregation process of beta-lactoglobulin (beta-LG) subjected to gamma irradiation are presented. Beta-LG in solutions of different protein concentrations (3 and 10 mg/ml) and in solid state with different water activities (a(w)) (0.22; 0.53; 0.74) was irradiated using a Cobalt-60 radiation source at dose level of 1-50 kGy. Small-angle X-ray scattering (SAXS) was used to study the conformational changes of beta-LG due to the irradiation treatment. The irradiated protein was also … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
26
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 29 publications
(35 citation statements)
references
References 40 publications
9
26
0
Order By: Relevance
“…There are no reported studies on either the conformational changes at secondary and tertiary structure level of irradiated b-LG, or how these changes influence the aggregation process. On the other hand, Oliveira et al (2007) verified that, when the protein was irradiated in the solid state (at different degrees of hydration, and at doses up to 50 kGy), the average size and compacity of the b-LG molecule did not change. These facts indicated that the conformational structure of the b-LG dimer was not affected by radiation (Oliveira et al, 2007).…”
Section: Introductionsupporting
confidence: 66%
See 2 more Smart Citations
“…There are no reported studies on either the conformational changes at secondary and tertiary structure level of irradiated b-LG, or how these changes influence the aggregation process. On the other hand, Oliveira et al (2007) verified that, when the protein was irradiated in the solid state (at different degrees of hydration, and at doses up to 50 kGy), the average size and compacity of the b-LG molecule did not change. These facts indicated that the conformational structure of the b-LG dimer was not affected by radiation (Oliveira et al, 2007).…”
Section: Introductionsupporting
confidence: 66%
“…The moisture content was 4.29 AE 0.02% and water activity 0.22 AE 0.01 (at 25 C). The preparation procedures of the b-LG samples with different water activities were described in Oliveira et al (2007).…”
Section: Preparation Of B-lg With Different a W And In Solutionmentioning
confidence: 99%
See 1 more Smart Citation
“…In practice doses, from 50 Gy up to kilograys are widely used, e.g., in radiotherapy treatment, in the manufacture of products derived from plasma (dose of 45 kGy inactivates all known blood-borne viruses), as well as in sterilization of the medical equipment and food products. The effects of irradiation at high doses of tens kGy on molecular, physicochemical, and functional properties of various proteins have been widely reviewed [2][3][4][5][6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…The influence of ionizing radiation on proteins has been the subject of great attention, and different techniques have been applied to study radiation-induced modifications in proteins [9,10]. Changes in peptide ions' abundance in serum after radiotherapy (51-72 Gy) as well as changes in serum proteome profiles are observed and expected to have a potential prognostic and predictive value in radiation therapy [18,19].…”
Section: Introductionmentioning
confidence: 99%